PENGARUH GAYA KEPEMIPINAN DAN KOMPETENSI TERHADAP KINERJA PEGAWAI PADA RUMAH SAKIT UMUM DAERAH BANDAR NEGARA HUSADA - Martina Martina; Iskandar Ali Alam (PT Saha Kreasi Indonesia, 2026)
This study aims to examine the influence of leadership style and competency on employee performance at Bandar Negara Husada Regional General Hospital (RSUD Bandar Negara Husada). The study was motivated by fluctuations in employee attendance, differences in competency levels, and the suboptimal implementation of leadership and coordination that may affect employee performance. A quantitative approach with an associative research design was employed. The study population consisted of 216 employees, from which 68 respondents were selected using the Slovin formula and the proportionate stratified random sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with Statistical Product and Service Solutions (SPSS). The findings indicate that leadership style has a positive and significant effect on employee performance, with a t-value of 5.641, a regression coefficient of 0.406, and a significance level of <0.001. Competency also has a positive and significant effect on employee performance, with a t-value of 7.651, a regression coefficient of 0.589, and a significance level of <0.001, making it the most influential variable in the model. Simultaneously, leadership style and competency have a positive and significant effect on employee performance, as indicated by an F-value of 41.749 and a significance level of <0.001. The Adjusted R Square value of 0.549 indicates that leadership style and competency jointly explain 54.9% of the variance in employee performance, while the remaining 45.1% is explained by other variables not included in this study. These findings suggest that strengthening leadership effectiveness and continuously developing employee competencies are essential strategies for improving employee performance and enhancing the quality of healthcare services at RSUD Bandar Negara Husada.